E-Commerce Between theory and practice - Boutine, Lakhdar; Bouaoune, Zakaria (Journal of Human Sciences, 2025)
This research focuses on studying the issue of e-commerce as a newly emerging form of commercial transactions and a manifestation of the knowledge economy, which has arisen as a result of modern technological developments. In this context, the importance of analyzing the adequacy of laws governing e-commerce in relation to the rapid global transformations in the field of information becomes evident. The aim of this research is to comprehensively review this topic and clarify its various dimensions, including the fundamental concepts that regulate the activity and development of e-commerce at the levels of companies, governments, and even individuals as electronic consumers. In the Algerian context, e-commerce is a relatively new practice, and its features have begun to take shape through Law 18-05 related to e-commerce. This law has provided multiple opportunities for online operators by establishing guarantees such as electronic advertising and adopting digital payment methods. Therefore, it is essential to highlight the reality of e-commerce in Algeria, along with its advancements and challenges.